Classroom Discourse Analysis: A Case of ESL Reading Class - Shahaji, Nurtimhar (International Journal of Language and Literary Studies, 2021)
More than the recognition, perception, and interpretation of written materials, reading has been dubbed as our bridge to other skills that are necessary for academic success. Subsequently, one way for teachers to monitor both the quantity and quality of output of the students is through Classroom discourse analysis, which is an aspect of classroom process research (Jiang, 2012). This paper, therefore, aimed to determine teacher’s questioning vis-à-vis students’ reading strategies in the case of an ESL reading class in one of the private schools in Zamboanga City, Philipenese through classroom discourse analysis. As a qualitative endeavor, it made use of classroom observations with the aid of an audio recorder to enable the analysis. A total of 131 exchanges were generated in a 45-minute discussion, with roughly 25 minutes allotted to the said discourse, and the rest for other activities. Teacher-Pupil-Teacher (TPT) captured as Teacher-Student-Teacher (TST) in the case of this paper, is the recurring sequence during the whole duration of the discourse. Discourse analysis that was done to an audio recording transcript of a reading class observation revealed patterns that are primarily present in some, if not most, discourse analysis (DA) research literature. Interestingly, it, however, uncovered the following: for teacher’s way of questioning (in this case, echoice and epistemic), epistemic questions (mostly, rhetorical for this matter), were made reference(s) by the students in answering questions. Consequently, the lesson or activity became, to some extent, communicative, because of the above mentioned points.